PENGARUH PEMBELAJARAN, HABITUASI DAN EKSTRAKURIKULER TERHADAP PEMBENTUKAN CIVIC DISPOSITION SISWA SMA NEGERI SE-KOTA BANDAR LAMPUNG - Erwin Susanto; Kokom Komalasari (Jurnal Ilmiah Mimbar Demokrasi, 2015)
This study purposed to describe how’s the influence of Civics learning, habituation and extracurricular towards civic disposition formation of students as the city of Bandar Lampung. This research used in this research is a quantitative approach with survey methods and correlational. The results showed that the learning Civics is positively significant affect on student’s civic dispositions at Senior High School in Bandar Lampung City. Habituation is positively significant affect on student’s civic dispositions at Senior High School in Bandar Lampung City. Extracurricular is positively significant affect on student’s civic dispositions at Senior High School in Bandar Lampung City. Simultaneously, learning Civics, habituations and extracurricular are positively significant affect on student’s civic dispositions at Senior High School in Bandar Lampung City.